DRAWING OF DETAILS OF DRESS AND DECORATIVE DECORATION OF MODELS - Ortiqova Ozoda Sharofovna (Bright Mind Publishing, 2025)
This article provides extensive information about drawing details of the dress and decorative decoration of models. At the same time, important ideas about the importance of decorative decoration of clothes were noted.
Keywords: dress, decoration, fabric, leather, image, texture, silhouette, wardrobe, vitochka, layma.